Green UMKM Development Policy According to Bank Indonesia's Perception of UMKM Development in East Nusa Tenggara Province - V. Liffu, Asnayati; Djani, William; Nursalam, Nursalam (Policy, Law and Political Research Center, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to Indonesia’s economy, especially in East Nusa Tenggara (NTT), where they contribute significantly to employment and GRDP. Despite their potential, particularly in agriculture and handicrafts, these sectors remain vulnerable to climate change and often lack environmentally friendly practices. In response, Bank Indonesia initiated the Green MSME development program to promote sustainable, inclusive, and circular economic practices. This study aims to analyze the relevance of Bank Indonesia's green MSME policies to the development of MSMEs in NTT and identify the supporting and inhibiting factors. Using a qualitative descriptive approach, data were collected through interviews, observations, and literature review in Kupang. Findings reveal BI NTT’s strategic role in promoting digitalization, green entrepreneurship training, and local resource-based clusters. However, challenges persist, including low environmental literacy, limited access to green financing, and weak infrastructure. Opportunities lie in NTT’s rich natural and cultural resources, which, if supported by cross-sector collaboration and contextual policies, can position green MSMEs as drivers of sustainable development. The study recommends strengthening policy implementation, contextual adaptation, and inter-agency synergy to accelerate green economic transformation in the region.